Measuring MLT winds by tracking meteor trails with incoherent scatter radar: a new method observes rapidly changing winds exceeding 500km/Hr - Oppenheim, Meers (2009)
Diapositivas presentadas en: CEDAR Workshop 2009 del 28 de junio al 2 de julio de 2009 en Santa Fe, Nuevo México, USA.